Fixed Dosing of Monoclonal Antibodies in Oncology - Hendrikx, Jeroen J.M.A.; Haanen, John B.A.G.; Voest, Emile E.; Schellens, Jan H.M.; Huitema, Alwin D.R.; Beijnen, Jos H. (The oncologist (Dayton, Ohio), 2017)
Most monoclonal antibodies in oncology are administered in body–size‐based dosing schedules. This is believed to correct for variability in both drug distribution and elimination between patients. However, monoclonal antibodies typically distribute to the blood plasma and extracellular fluids only, which increase less than proportionally with the increase in body weight. Elimination takes place via proteolytic catabolism, a nonspecific immunoglobulin G elimination pathway, and intracellular degradation after binding to the target. The latter is the primary route of elimination and is related to target expression levels rather than body size. Taken together, the minor effects of body size on distribution and elimination of monoclonal antibodies and their usually wide therapeutic window do not support body–size‐based dosing. We evaluated effects of body weight on volume of distribution and clearance of monoclonal antibodies in oncology and show that a fixed dose for most of these drugs is justified based on pharmacokinetics. A survey of the savings after fixed dosing of monoclonal antibodies at our hospital showed that fixed dosing can reduce costs of health care, especially when pooling of preparations is not possible (which is often the case in smaller hospitals). In conclusion, based on pharmacokinetic parameters of monoclonal antibodies, there is a rationale for fixed dosing of these drugs in oncology. Therefore, we believe that fixed dosing is justified and can improve efficiency of the compounding. Moreover, drug spillage can be reduced and medication errors may become less likely. Implications for Practice The currently available knowledge of elimination of monoclonal antibodies combined with the publicly available data from clinical trials and extensive population pharmacokinetic (PopPK) modeling justifies fixed dosing. Interpatient variation in exposure is comparable after body weight and fixed dosing and most monoclonal antibodies show relatively flat dose‐response relationships. For monoclonal antibodies, this results in wide therapeutic windows and no reduced clinical efficacy after fixed dosing. Therefore, we believe that fixed dosing at a well‐selected dose can increase medication safety and help in reduction of costs of health care without the loss of efficacy or safety margins. In the field of oncology, most drugs are administered in a body–size‐based dosing schedule instead of a fixed dose for all patients. This article presents the advantages of fixed dosing of monoclonal antibodies, arguing in favor of fixed dosing schemes for all currently approved antibodies in oncology.